2016
DOI: 10.1186/s41182-016-0014-9
|View full text |Cite
|
Sign up to set email alerts
|

Criteria of “persistent vomiting” in the WHO 2009 warning signs for dengue case classification

Abstract: IntroductionDengue is a viral disease that spreads rapidly in the tropic and subtropic regions of the world and causes 22,000 deaths annually. In 2009, the World Health Organization (WHO) released a new classification of dengue infections, which divided them into three categories: dengue without warning sign (D), dengue with warning sign (DWS), and severe dengue (SD). However, researchers have been using different criteria to define persistent vomiting; therefore, we aimed to evaluate the ability of the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…12 In the present study vomiting is associated with 56.00% which slightly higher compared to a study conducted by Vuong NL et al, who found that vomiting is associated with 44.00%. 13 In the present study joint pain is associated with 69.00%. The exact pathogenesis of joint pain in dengue infection is not precisely known.…”
Section: Discussionsupporting
confidence: 56%
“…12 In the present study vomiting is associated with 56.00% which slightly higher compared to a study conducted by Vuong NL et al, who found that vomiting is associated with 44.00%. 13 In the present study joint pain is associated with 69.00%. The exact pathogenesis of joint pain in dengue infection is not precisely known.…”
Section: Discussionsupporting
confidence: 56%
“…When the vomiting signs were compared between the groups with or without dengue and with or without warning signs (D/DWS) versus those with SD, the severe dengue group had a significantly higher prevalence of vomiting signs and also a higher median number of vomiting episodes. 11 Vuong et al 11 reported that persistent vomiting is as an early sign for the detection of SD infection. It showed that the frequency of vomiting signs was significantly higher among patients in the SD group (92%, 11/12) than among patients in the D/DWS group (49%, 33/67), and the median number of vomiting episodes per day was also significantly higher in the SD group (2.5, range: 2-3) than in the D/DWS group (0, range: 0-2).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the study found that persistent vomiting was associated with the development of SD in 54% of the patients (OR 12.0), and the number of two or more vomiting episodes per day while predicting SD among the D/DWS group of patients showed good sensitivity (92%) and specificity (52%). 11 Shock with or without respiratory distress has been reported to be the most frequent complication in patients with SD that was caused by a clinical fluid accumulation. 9 In the present study, clinical fluid accumulation was found in 20 patients with NSD infection and 21 patients with SD infection.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous study was reported the prevalence of vomiting symptom was higher in severe dengue group than dengue infection/dengue infection with warning sign group. 20 Persistent vomiting is one warning sign according to WHO 2009. 1 Ledika et al held study in patients with severe dengue showed persistent vomiting had correlated with severe dengue.…”
Section: Resultsmentioning
confidence: 99%